The relationship between daily positive future thinking and past-week suicidal ideation in youth: An experience sampling study - Kirtley, Olivia J.; Lafit, Ginette; Vaessen, Thomas; Decoster, Jeroen; Derom, Catherine; Gülöksüz, Sinan; De Hert, Marc; Jacobs, Nele; Menne-Lothmann, Claudia; Rutten, Bart P. F.; Thiery, Evert; van Os, Jim; et al. (Frontiers in Psychiatry, 2022)
Reduced positive future thinking has been associated with suicidal ideation and behaviour in adults, and appears to be exacerbated by negative affect. Yet, this has received little attention in youth. Prior research has also focussed on longer-term future thinking, e.g. months and years, and relied on lab-based assessments. Using the experience sampling method (ESM), we investigated whether short-term future thinking in daily life was associated with suicidal ideation in youth and explored the role of affect in the future thinking – suicidal ideation relationship. A community sample of N= 722 adolescent twins and their non-twin siblings completed ESM as part of the TwinssCan study (n= 55 with, and n= 667 without, past-week suicidal ideation). Participants completed self-report questionnaires, including on past-week suicidal ideation as part of the SCL-90. Subsequently, daily future thinking was assessed each morning for six days with ESM. To investigate the relationship between daily positive future thinking and past-week suicidal ideation, we estimated a mixed-effects linear regression model with a random intercept for participant, including age and sex as covariates. The relationship between daily positive future thinking, past-week suicidal ideation, and average positive and negative affect from the previous day was investigated by estimating two separate mixed-effects linear regression models (one for negative affect, one for positive affect), with a random intercept for participant, and random slopes for average positive and negative affect. Our results showed that participants reporting higher past-week suicidal ideation also reported significantly less daily positive future thinking during the ESM period, and this association remained significant when controlling for previous-day average positive and negative affect. Higher average positive affect from the previous day was significantly associated with higher positive future thinking. Although average negative affect from the previous day was associated with lower positive future thinking, this association was not statistically significant. Our findings indicate that short-term future thinking relates to suicidal ideation among a non-clinical sample of adolescents. Future research should investigate the directionality of the future thinking – suicidal ideation relationship, in order to investigate whether impaired future thinking may be an early warning signal for escalating suicidal ideation in youth.